(untitled) (Journal of the College of Basic Education, 2022)
For years, fears about Kurdish separatism and ambiguity toward the regime of Saddam Hussein and its successors defined Turkey’s relationship with Iraq. Nonetheless, after the 1991 Gulf war,Turkey allowed U.S. and British planes flying from In cirlik Air Base in southeast Turkey to enforce a no-fly zone over northern Iraq (Operation Provide Comfort/Operation Northern Watch) in order to protect Iraq’s Kurds from Saddam Hussein and to monitor Iraq’s armed forces. This protective shield enabled an autonomous Iraqi Kurdish administration to develop despite Turkish unease about its potential as a role model for Turkish Kurds. Turkish leaders later expressed doubts about U.S. regime change plans for Iraq before the 2003 invasion and, on March 1, 2003, the Turkish parliament refused to authorize the deployment of U.S. forces to Turkey for the purpose of opening a northern front against Iraq.